2018
DOI: 10.1007/s40615-018-0526-6
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Social Patterning of Postpartum Depression by Immigration Status in Canada: an Exploratory Review of the Literature

Abstract: Postpartum depression (PPD) refers to a woman's experience with any depressive episode occurring within the first year of the postpartum period (Stewart et al., 2008;53(2):121-4). While PPD is a global phenomenon, the distribution of PPD within populations is not universal. Indeed, evidence from the Canadian literature confirms a significant disparity in PPD outcomes, as the prevalence rate of PPD is markedly increased among immigrant women (Stewart et al., 2008;53(2):121-4), and immigration status emerges as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…According to Gheorghe et al 23 (p247) one in four women who gave birth in Canada between January 1 and June 30, 2018, reported symptoms consistent with PPA or PPD ve to thirteen months postpartum". Similarly, Saad 24 illustrated that the literature reveals an increased prevalence of postpartum depression in immigrant women in Canada mediated by risk factors linked to social determinants of health such as social support, socioeconomic status, and life stressors. About this point, we cannot provide statistical data among our participants, but we can highlight that mental health was identi ed as a main theme for our project due to frequent mentions of related issues and experiences among our sample which underline the relevance of addressing mental health issues during pregnancy and postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…According to Gheorghe et al 23 (p247) one in four women who gave birth in Canada between January 1 and June 30, 2018, reported symptoms consistent with PPA or PPD ve to thirteen months postpartum". Similarly, Saad 24 illustrated that the literature reveals an increased prevalence of postpartum depression in immigrant women in Canada mediated by risk factors linked to social determinants of health such as social support, socioeconomic status, and life stressors. About this point, we cannot provide statistical data among our participants, but we can highlight that mental health was identi ed as a main theme for our project due to frequent mentions of related issues and experiences among our sample which underline the relevance of addressing mental health issues during pregnancy and postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…Women's migratory status and language spoken at home were associated with mentor type. In a narrative review of mechanisms underlying social patterning of PPD in immigrant women, Saad (30) reported that loss of previous support networks and challenges forming new networks after immigration may underlie increased rates of postnatal depression among immigrant women. This mechanism may apply to women who relocate within a country and lose previous social networks and sense of community belonging.…”
Section: Discussionmentioning
confidence: 99%